Recent trends in term trial of labor after cesarean by number of prior cesarean deliveriesAJOG Global Reports at a Glance - Beth L. Pineles, MD, PhD; Cara M. Buskmiller, MD; Emma J. Qureshey, MD; Angela J. Stephens, MD; Baha M. Sibai, MD (Elsevier, 2023)
BACKGROUND: Cesarean delivery is a major source of maternal morbidity, and repeat cesarean delivery accounts for 40% of cesarean delivery, but recent data on the trial of labor after cesarean and vaginal birth after cesarean are limited. OBJECTIVE: This study aimed to report the national rates of trial of labor after cesarean and vaginal birth after cesarean by number of previous cesarean deliveries and examine the effect of demographic and clinical characteristics on these rates. STUDY DESIGN: This was a population-based cohort study using the US natality data files. The study sample was restricted to 4,135,247 nonanomalous singleton, cephalic deliveries between 37 and 42 weeks of gestation, with a history of previous cesarean delivery and delivered in a hospital between 2010 and 2019. Deliveries were grouped by number of previous cesarean deliveries (1, 2, or ≥3). The trial of labor after cesarean (deliveries with labor among deliveries with previous cesarean delivery) and vaginal birth after cesarean (vaginal deliveries among trial of labor after cesarean) rates were computed for each year. The rates were further subgrouped by history of previous vaginal delivery. Year of delivery, number of previous cesarean deliveries, history of previous cesarean delivery, age, race and ethnicity, maternal education, obesity, diabetes mellitus, hypertension, inadequate prenatal care, Medicaid payer, and gestational age were examined concerning the trial of labor after cesarean and vaginal birth after cesarean using multiple logistic regression. SAS software (version 9.4) was used for all analyses. RESULTS: The trial of labor after cesarean rates increased from 14.4% in 2010 to 19.6% in 2019 (P<.001). This trend was seen in all categories of number of previous cesarean deliveries. Moreover, vaginal birth after cesarean rates increased from 68.5% in 2010 to 74.3% in 2019. The trial of labor after cesarean and vaginal birth after cesarean rates were the highest for deliveries with a history of both 1 previous cesarean delivery and a vaginal delivery (28.9% and 79.7%, respectively) and the lowest for those with a history of ≥3 previous cesarean deliveries and no history of vaginal delivery (4.5% and 46.9%, respectively). Factors associated with the trial of labor after cesarean and vaginal birth after cesarean rates are similar, but several factors have different directions of effect, such as non-White race and ethnicity, which is associated with a higher likelihood of trial of labor after cesarean but a lower likelihood of successful vaginal birth after cesarean. CONCLUSION: More than 80% of patients with a history of previous cesarean delivery deliver by repeat scheduled cesarean delivery. With vaginal birth after cesarean rates increasing among those who attempt a trial of labor after cesarean, emphasis should be put on safely increasing the trial of labor after cesarean rates.